The Relationship Between Coffee Consumption and The Incident of Gastritis in Adolescents at Siere Cendekia Vocational School - Mukhaira, Inna; Nurmayanti, Selpi; Pujiningtyas, Setiarini (Journal of Applied Food and Nutrition, 2023)
Background: Based on the 2019 Health Profile, gastritis is one of the 10 most common diseases in hospitalized patients in Indonesia with 4.9% of cases. The results of the Health Profile of the Tangerang Health Service were 30%. Indonesian coffee consumption throughout the 2016-2021 period is predicted to grow by an average of 8.22%/year. In 2021, coffee supply is predicted to reach 795 thousand tons with consumption of 370 thousand tons, resulting in a surplus of 425 thousand tons. The aim of the research was to determine the relationship between coffee consumption and the occurrence of gastritis in Siere Cendekia Vocational Schooladolescents.Research Methods: This research uses a cross sectional method. The research sample was 140 respondents using the Proportionate Stratify Randpm Sampling technique..Research Result: Analysis of the relationship between high coffee consumption showed that there were 74 respondents (52.9%) who had problems with gastritis. Meanwhile, there were 66 students (47.1%) who had low coffee consumption.Conclusion: There is a relationship between coffee consumption and the incidence of gastritis in Siere Cendekia Vocational Schooladolescents.